Heterogeneous Responses of Chinese Cities＇ Housing Prices to Monetary Policies - 闫妍 王延颋 朱晓武 (Communications in theoretical physics, 2011)
This works examine the responses of housing prices to the monetary policies in various Chinese cities. Thirty-five large and medium sized Chinese cities are classified into six clusters applying the minimum variance clustering method according to the calculated correlation coefficients between the housing price indices of every two cities. Time difference correlation analysis is then employed to quantify the relations between the housing price indices of the six clusters and the monetary policies. It is suggested that the housing prices of various cities evolved at different paces and their responses to the monetary policies are heterogeneous, and local economic features are more important than geographic distances in determining the housing price trends.